Regional Heterogeneity of Income Tax in the Russian Federation: The Experience of the Quantitative Analysis and Regulatory Issues - Dzhurbina, Elena M.; Fateev, Dmitriy I. (International Review of Management and Marketing, 2016)
The paper implemented a comprehensive economic and statistical analysis of heterogeneity of tax revenues in the regions of the Russian Federation, revealing the contradictory trends of reducing differentiation in tax bases while increasing unevenness in tax revenues. The study identified the basic factors and causes of differentiation of income by certain types of taxes. The prospects of regulation of regional heterogeneity based on the transformation of the order of transfer of taxes through the levels of the budget system is critically evaluated. Keywords: tax revenues, gross regional product, regional development JEL Classifications: C21, H71, R10